IDEATION TAXONOMIC RELATION OF HATA PANGUPA GRADUATION CEREMONY IN PADANGSIDIMPUAN - mutia nasution (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
This study deals with the types of taxonomic of Hata Pangupa graduation Ceremony in Padangsidimpuan. The objectives of this study are to describe the types of taxonomic relation occrued in Hata Pangupa graduation Ceremony in Padangsidimpuan, to analyze the relation of taxonomic relation in Hata Pangupa graduation Ceremony in Padangsidimpuan, to explain out the reasons why the taxonomic relations describe in the way they are. It presented a qualitative data analysis. The source of the data was taken from the video recorded. The data analysis found out the findings that four types of taxonomic relation were used in Hata Pangupa graduation Ceremony in Padangsidimpuan. The kinds that were used are repetition, synonym, contrast: series (opposition), class: class-member and co-class. Whereas, the contrast: series (cycles), and part: co-part did not use by Mora, Kahanggi and Anak Boru in Hata Pangupa Wedding Ceremony in Tapanuli Selatan. The process were showed the reference chains, they are personal and demonstrative. Hata Pangupa has an institution spoken by specialist speakers and it is part of social interaction, religion and traditional custom.